Strategi Pembinaan Dan Pengembangan Profesionalisme Guru Pendidikan Agama Islam Di Sekolah dan Madrasah - Yoyo Rodiya; Suklani Suklani (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
The purpose of this study was to understand the professionalism problems of Islamic Religious Education teachers and to understand the strategies for fostering and developing the professionalism of Islamic Religious Education teachers in schools and madrasas. The results of the study show that our national education is still facing various educational problems, including the low quality of educational processes and outcomes and the weak professionalism of Islamic Religious Education teachers in schools and madrasas. To overcome these problems, it is necessary to foster and develop the professionalism of Islamic Religious Education teachers with the following strategies: 1) Self-development, in the form of functional/technical education and training through training, upgrading, technical guidance, apprenticeships, courses and so on, and collection activities teachers through scientific activities in teacher professional organizations, seminars, workshops, colloquiums, discussion panels, in-house training and so on. 2) Scientific publication activities in the form of reporting in scientific forums, publication of research results, publication of textbooks, teacher guides and others in the field of formal education. 3) Innovative work in the form of finding appropriate technology, creating works of art, making or modifying props and practicum tools and so on.